Role of intellectual capital on creation of innovation capabilities in HIS and computer units - Sayed Mehdi Hejazi; Samira Yadegari; Nafiseh Hajrahimi (Wolters Kluwer Medknow Publications, 2018)
Introduction: Simultaneously along with information technology progress, knowledge has considered as a fundamental base for economic growth for the time being. In today's knowledge-based economy, production and exploitation of knowledge play the main roles in the process of wealth creation. The current revolution in information technology has given new light to the importance of knowledge such that it has now become the base of economy in today's world. In today's knowledge-based economy, production and exploitation of knowledge play the main roles in the process of wealth creation. Considering key contributions of knowledge management in competitiveness of organizations and their entry into global arenas, this study sought to evaluate the impact of different aspects of intellectual property on innovations in computer and health information system (HIS) units at selected medical center in the city of Isfahan during 2015. Objectives: The present study seeks to evaluate the impact of different aspects of intellectual property on innovations in computer and HIS units at selected medical centers in the city of Isfahan during 2015 (2015). Settings and Design: Population of this research includes staff working in computer and HIS units of 10 medical centers. Data were collected using a questionnaire made by the researcher. A written questionnaire (also referred to as self-administered questionnaire) is a data collection tool in which written questions are presented that are to be answered by study individuals, where for the case of the present study include staff members working at computer and HIS units of 10 medical centers. Materials and Methods: In the first stage, medical factors were determined by experts of Isfahan University of Medical Sciences as intellectual property. Factors were then distributed randomly among 100 employees during a survey, after considering their validity and reliability. Statistical Analysis: Descriptive and inferential statistics were used for data analysis. Results: Data analysis showed that innovation is one of the most important indicators of intellectual capital in computer and HIS units of medical centers and has a higher than average importance. Conclusions: The results of this study, in addition to providing guidelines in the management of intellectual capital in Isfahan province hospitals, can be used as a model for improving innovation in hospitals and understanding various factors affecting organizational innovation.